Ductility performance of wall-slab joint in Industrialized Building System (IBS) subjected to lateral reversible cyclic loading / Mohd Ashaari Masrom, Nor Hayati Abdul Hamid and Mohd Azrizal Fauzi - Masrom, Mohd Ashaari; Abdul Hamid, Nor Hayati; Fauzi, Mohd Azrizal (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Connections between floor slab and shear walls constitute an essential link in the lateral load-resisting mechanism of slab-wall of reinforced concrete building. The ductility performance of wall-slab joint influences the pattern and distribution of lateral forces among the vertical elements of a structure. This study presents the results of an experimental investigation on the ductility performance of wall-slab connection which is designed in accordance to BS 8110. The experiment work includes full-scale test of wall-slab connection under reversible lateral cyclic loading. This study focuses on ductility performance of wall-slab connection under reversible cyclic loading. The hysteresis loops was developed based on experiment data to determine the ductility of wall-slab joint under reversible cyclic loading. The theoretical background was formulated to validate the result of experiment. There was a good agreement between them. Therefore, the ductility of the joint was determined and designed accordingly. The results indicate that the wall-slab connection was governed by brittle failure modes in reinforced concrete. This is due to low ductility which resulted in the inability of the connection to absorb energy efficiently and therefore further undergoes inelastic deformation. In fact, the brittle failure modes did not allow the energy dissipation and lead to sudden failure without warning to the structures as experienced by the Reinforced Concrete (RC) buildings during earthquakes